(Effects of Distillation Time and Seed Crushing on The Yield and Physico-Chemical Properties of Cumin Oil) - Sudibyo, Agus (Balai Besar Industri Agro, 1989)
A study on the effects of distillation time and seed crushing on the yield and physico-chemical properties of cumin oil has been conducted. Two treatments were given to cumin seed i.e.(a) remain whole, and (b) crushed (using blender). The seeds were distilled using cohobation methods for 3,5 and 7 hours. The yield of whole seeds were 1.90; 2.10 and 2.23% for each distillation time, while those of crushed seeds were 2.18; 2.25 and 2.43% respectively. The evaporation residues of both oils were increased from ca. 0.18% (3 hrs. distillation) to 2.23% (7 hrs distillation). an from ca. 0.20% (3 hrs. distillation) to 0.26% (7 hrs distillation). The highest cuminaldehyde content was obtained from 3 hrs. distillation (5.99%) and the lowest was those of 7 hrs. distillation (45.14%).